Assessing the Sharia Compliance of Hotel Facilities and Services in East Java: A Comparative Analysis of National and International Standards - Rahmawati, Lilik; Pratikto, Muhammad Iqbal Surya; Wigati, Sri; Muflihin, Muhammad Dliyaul; Rahmani, Nur Maulidah Dini; Muntazeri, Eliya Najma (El-Qist: Journal of Islamic Economics and Business (JIEB), 2025)
This study aims to examine the compliance of Sharia-compliant hotels in East Java, Indonesia, with both national standards (DSN-MUI Fatwa No. 108/2016) and international benchmarks (CrescentRating and Salam Standard). Utilizing a qualitative methodology involving field observations and semi-structured interviews across three hotels—Namira Syariah Surabaya, Radho Syariah Malang, and Walan Syariah Sidoarjo—the research reveals partial yet consistent alignment with core Sharia hospitality principles. These include the prohibition of immoral activities, availability of prayer amenities, and the absence of alcohol and gambling. However, the integration of Islamic financial institutions remains absent across all hotels, indicating a gap in full Sharia compliance as defined nationally. From an international perspective, all hotels meet the "Accommodates" level (Level 4) under CrescentRating and correspond to Silver or Gold tiers in the Salam Standard. This study contributes to global halal tourism scholarship by offering a multi-framework compliance assessment model that can guide policy formulation and standardization efforts in Muslim-friendly destinations. It also emphasizes the urgent need for unified regulatory frameworks, formal certification, and integration of Islamic finance within the halal hospitality sector. Future research should extend this analysis to higher-rated hotels and conduct cross-regional comparisons to assess consistency in compliance and service quality.